EFFECTS OF SALT STRESS ON VEGETATIVE PROPAGATION OF Pterocarpus santalinoides L’Hérit. ex DC. - Fredrick, C.; Chima, U. D.; Alex, A.; Emeka, B. I. (RENEWABLE, 2024)
The influence of salt stress on sprout length, collar diameter, leaf and branch production, and survival rate of Pterocarpus santalinoides stem cuttings was assessed. In a completely randomized design with five treatments: (0, 5, 10, 15 and 20 grams of salt), 20 cuttings were exposed to each of the five salt solutions. Data were analyzed using descriptive and inferential statistics. There were significant differences in the growth variables across treatments. However, sprout length at six weeks, did not significantly differ. Growth variables decreased with increase in salt stress, with control and 20 g displaying the highest and lowest growth attributes, respectively. Seedlings in control treatments had the highest sprout length (20.65 mm, 28.30 mm, 32.15 mm and 40.35 mm) at 6, 8, 10 and 12 weeks, respectively, while 20 g treatment had the least (15.95 mm, 17.78 mm, 19.80 mm and 25.80 mm). Number of leaves (13.25, 18.75, 22.13 and 36.13), branches (3.50, 4.88, 7.50 and 9.25) and collar diameter (3.50 mm, 4.88 mm, 7.50 mm and 9.25 mm) were highest for control over the 6, 8, 10 and 12 weeks. Stem cuttings of Pterocarpus santalinoides may not thrive well in saline soils, because of the negative effects of salt on seedlings.